Spontaneous rupture of the bladder during vomiting - Crawford, Ruairidh (BMJ Case Rep, 2017)
A 46-year-old woman with no urological history or comorbidities presented with an acute abdomen with haematuria after a spell of protracted vomiting. The initial cystogram was negative; however, CT imaging highly suggested an intraperitoneal bladder perforation, which was confirmed during laparotomy and subsequently repaired. Cystoscopic evaluation prior to laparotomy revealed no concurrent bladder pathology, and the ureteric orifices were intact. A cystogram 2 weeks after repair demonstrated no leaks, and her catheters were removed. She recovered well, with expectant postoperative pain and lower urinary tract symptoms settling on 3-month review. Spontaneous bladder rupture is a rare entity, with very few reports in the literature.